PTSD in those who care for the injured. Issue 2 (February 2017) - Luftman, Kevin; Aydelotte, Jayson; Rix, Kevin; Ali, Sadia; Houck, Katherine; Coopwood, Thomas B.; Teixeira, Pedro; Eastman, Alex; Eastridge, Brian; Brown, Carlos V.R.; Davis, Matthew
Abstract: Background: Post Traumatic Stress Disorder (PTSD) has become a focus for the care of trauma victims, but the incidence of PTSD in those who care for injured patients has not been well studied. Our hypothesis was that a significant proportion of health care providers involved with trauma care are at risk of developing PTSD. Methods: A system-wide survey was applied using a modified version of the Primary Care PTSD Screen [PC-PTSD], a validated PTSD screening tool currently being used by the VA to screen veterans for PTSD. Pre-hospital and in-hospital care providers including paramedics, nurses, trauma surgeons, emergency medicine physicians, and residents were invited to participate in the survey. The survey questionnaire was anonymously and voluntarily performed online using the Qualtrix system. Providers screened positive if they affirmatively answered any three or more of the four screening questions and negative if they answered less than three questions with a positive answer. Respondents were grouped by age, gender, region, and profession. Results: 546 providers answered all of the survey questions. The screening was positive in 180 (33%) and negative in 366 (67%) of the responders. There were no differences observed in screen positivity for gender, region, or age. Pre-hospital providers were significantly more likely to screen positive for PTSD compared to the in-hospital providers (42% vs. 21%, P < 0.001). Only 55% of respondents had ever received any information or education about PTSD and only 13% of respondents ever sought treatment for PTSD. Conclusion: The results of this survey are alarming, with high proportions of healthcare workers at risk for PTSD across all professional groups. PTSD is a vastly underreported entity in those who care for the injured and could potentially represent a major problem for both pre-hospital and in-hospital providers. A larger, national study is warranted to verify these regional results.